(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Our study illustrates the histomorphological features of the intestine of frogs living in different surrounding areas of the Hrazdan River characterized by different degrees of pollution. The intestinal epithelium of frogs living near the most polluted parts of the river (villages Darbnik and Geghanist) illustrates phenomena of pyknotic changes and necrosis, the presence of a great number of lymphocytes and lymphoid tissue accumulations in the epithelium. An increasing amount of fibroblasts is observed in the mucous membrane. Our study indicates the increased activation process of the mast cells and the presence of their accumulations in submucosal layers of the intestines of frogs living in the most polluted parts of the river.